Tunable 2.0 µm Q-switched fiber laser using a silver nanoparticle based saturable absorber. (11th May 2017) - Ahmad, H; Samion, M Z; Muhamad, A; Sharbirin, A S; Shaharuddin, R A; Thambiratnam, K; Norizan, S F; Ismail, M F
Abstract: A thulium-doped fiber laser (TDFL) with a tunable Q-switched output is proposed and demonstrated. A silver nanoparticle based saturable absorber is used to generate the Q-switched pulses, while a tunable Mach–Zehnder filter acts as the wavelength-tuning mechanism. The TDFL has an operating wavelength range of 1916.5–1945.3 nm, with output pulses that have a repetition rate of 50.1 kHz and a pulse width of 5.1 µ s, as well as a pulse energy of 69.3 nJ at the maximum pump power. The Q-switched pulses obtained are very stable and have a signal-to-noise ratio of 34.18 dB.